Hybridization, missing wild ancestors and the domestication of cultivated diploid bananas - Sardos, Julie; Breton, Catherine; Perrier, Xavier; Houwe, Ines van den; Carpentier, Sebastien C.; Paofa, Janet; Rouard, Mathieu; Roux, Nicolas Stephan M. (Frontiers Media, 2022)
Hybridization and introgressions are important evolutionary forces in plants. They contribute to the domestication of many species, including understudied clonal crops. Here, we examine their role in the domestication of a clonal crop of outmost importance, banana (Musa ssp.). We used genome-wide SNPs generated for 154 diploid banana cultivars and 68 samples of the wild M. acuminata to estimate and geo-localize the contribution of the different subspecies of M. acuminata to cultivated banana. We further investigated the wild to domesticate transition in New Guinea, an important domestication center. We found high levels of admixture in many cultivars and confirmed the existence of unknown wild ancestors with unequal contributions to cultivated diploid. In New Guinea, cultivated accessions exhibited higher diversity than their direct wild ancestor, the latter recovering from a bottleneck. Introgressions, balancing selection and positive selection were identified as important mechanisms for banana domestication. Our results shed new lights on the radiation of M. acuminata subspecies and on how they shaped banana domestication. They point candidate regions of origin for two unknown ancestors and suggest another contributor in New Guinea. This work feed research on the evolution of clonal crops and has direct implications for conservation, collection, and breeding.